Characterization of biomaterials commonly used in dentistry for bone augmentation by X‐ray and electron techniques. (7th November 2016) - Limandri, S.; Fernandez Bordín, S. P.; Gersberg, M.; Brito, L.; Oliveira, R. G.; Fouga, G.; Galván Josa, V.
Abstract : Hydroxyapatite (HA), beta‐tricalcium phosphate and bioactive glasses are commonly used as reabsorbable biomaterials, mainly in orthopaedics and dentistry. The performance of each material depends on many factors, in particular, on their chemical and phase composition, microstructure, granule size and pore volume. For this reason, it is important to have a full characterization that allows correlating these properties with the material biological behaviour. In this work, three commercial samples of materials currently used in dentistry as bone substitutes were characterized. Granules corresponding to bovine and synthetic HA and bioactive glass 45S5 type were studied by scanning electron microscopy, conventional and synchrotron radiation X‐ray diffraction and X‐ray fluorescence. The specific surface area was also obtained by the Brunauer, Emmett and Teller method. We observed that Ca/P molar ratios for both HAs are higher than the value corresponding to the stoichiometric HA. The coherent domain obtained for the bovine HA is larger along the c axis crystal direction, and it is around 15 times lower than the value corresponding to the synthetic HA. The specific surface area for the bovine HA is one of the highest values reported in literature. Low amounts of crystalline CaO were observed only for the synthetic HA sample. Crystalline combeite and wollastonite were detected for the bioactive glass sample and quantified by using rutile as internal standard. The relation between the physico‐chemical characterization performed in this work and the potential biological response of the materials is discussed in terms of the information available in literature. Copyright © 2016 John Wiley & Sons, Ltd.